Financial Literacy and Its Effect on Business Performance of Student-Driven Entrepreneurship in The Covid 19 Pandemic - Rachmawati, Rina; Ardiansari, Anindya; Kriswanto, Hendra Dedi (Indonesian Journal of Business and Entrepreneurship, 2022)
The objective of this research is to empirically examine the role of financial literacy and its influence on business performance in the university entrepreneurial students. The research population is entrepreneurship students at Universitas Negeri Semarang (Unnes) with a total of 1215 SMEs with the sample being 105 respondents. The collected data were analyzed using a structural equation model based on Partial Least Squares. The analytical tool used is Smart PLS 3.0 software. The results found that several obstacles faced by student-operated SMEs were found lack of knowledge about business management, especially finance, lack of professional assistance, time allocation constraints that clashed with lectures and motivational constraints to always be consistent in entrepreneurship. The results of the study concluded that financial knowledge, financial attitudes and financial behavior each had a positive effect on the entrepreneurial business performance of student-operated SMEs. The results underscored the need for social support from the universities to boost financial entrepreneurship and financial literacy among entrepreneurial students. Keywords: business performance, entrepreneurial students, financial literacy, student organizations, SMEs